PERANCANGAN ULANG USER INTERFACE (UI) USER EXPERIENCE (UX) SIPLO (SISTEM INFORMASI TERPADU LAYANAN PRODI) DENGAN METODE DESIGN THINKING BERBASIS MOBILE - Kusumawardani, Aditya Putri; Setyadi, Hario Jati; Jundillah, Muhammad Labib (LPPM Universitas Bina Bangsa, 2024)
SIPLO is an Integrated Information System for Study Program Services that contains academic data of students, lecturers, and data from study programs. This system has features to make it easier for users to upload new data. However, its complex appearance makes it difficult to access via the mobile website. This study aims to redesign the user interface to suit student needs and improve the user experience of the SIPLO mobile website. The Design Thinking method is used with data sources from usability testing and in-depth interviews. The result is a new design for the SIPLO mobile website that gets a SUS score of 82.6 in the excellent category.